Religious motives and reminiscences in the poetry of kazakh akyn-zhyraus (Journal of Philosophy, Culture and Political Science, 2022)
The poetry of akyn-zhyraus is the most important stage in the formation of aesthetic principles, canons, and traditional formula language of all Kazakh poetry. The authority of poetry of five centuries (XIV-XIX centuries) was unshakable until XX century and created the basis of both epic and lyrical Kazakh poetry, the transformation of which began only in XX century. One of the most important principles of Zhyrau's poetry was spirituality, a deep connection with the religious and mythological principle, rooted in ancient beliefs andarchaic worldview systems. As the analysis shows, spiritual syncretism was peculiar for Zhyraus of the ХIV–ХVI centuries when tengrian, animistic relicts and Islamic motives and concepts were consistently united in the worldview.This syncretism is especially vividly appeared in the poetry of Asan-kaigy, Dospambet and Shalkiyiz zhyrau. In the era of the Kazakh-Jungar wars, in the XVI - XVIII centuries, which contributed to the spiritual consolidation of the Kazakh people, Islamic motives strengthened in the poetry of Zhyrau, which was manifested in the active penetration of Muslim vocabulary into the poetry of Zhyrau, reminiscence functionality, quotations, and appeals in God’s names. This tendency is most characteristic to the poetry of Bukhar Zhyrau, who was not only a poet- preacher but to some extent, was also the spiritual leader of the people.The article starts with an introduction to the concepts in the poetry of the akyn-zhyraus which is not studied sufficiently in Kazakhstani context. Then, moves to methodology section that is based on the principles of comparative, systematic and historical-literary methods. Later, the authors continue discussing the findings which are followed by the conclusion section at the end.Key words: Kazakhstan, akyn-zhyraus, comparative, motives, myth-poetics.